PENGEMBANGAN DESA WISATA BERBASIS KEARIFAN LOKAL SEBAGAI STRATEGI PENGENTASAN KEMISKINAN DI KABUPATEN KLUNGKUNG - Dewa Ayu Eka Agustini; I Wayan Landrawan; I Nyoman Pasek Hadisaputra (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2023)
This study aims to find out, understand and analyze (1) the form of tourism recovery affected by the pandemic through the development of tourism villages based on local wisdom; (2) recovery of tourism affected by the pandemic through the development of tourism villages based on local wisdom in its application as a poverty alleviation strategy in Klungkung Regency; and (3) the implications of implementing the recovery of tourism affected by the pandemic through the development of tourism villages based on local wisdom as a poverty alleviation strategy in Klungkung Regency. This type of research is field research, using an approach to empowering the poor through an approach and public awareness is needed so that they can use and have access to control in the development of tourist villages. Secondary data is data that is used as supporting material for research preparation. Data collection techniques in this study include literature study, observation, and interviews. The data analysis of this research includes quantitative descriptive analysis and qualitative descriptive analysis. The results of this study indicate that there is no maximum development of tourism villages based on local wisdom as an effort to alleviate poverty to overcome the powerlessness of the poor caused by limited access, lack of knowledge and skills, trapped in poverty (poverty trap) and community powerlessness. Therefore, further development is needed to realizing community independence in tourism villages in Klungkung Regency, especially increasing the involvement and active participation of the community in various income and welfare activities as well as the utilization of tourist villages by the community and local government. The strategy of developing a tourism village based on local wisdom in Klungkung Regency needs to pay attention to things, including the marketing of tourism village packages that show the selling value of the village, sustainable management of tourist villages and preserving the tourism village itself as part of the potential of the tourist village.